(untitled) (Research, Society and Development, 2022)
The aim of the present study was to analyze how information carriers on social networks affect the induction of eating disorders, and how the internalization of social norms conveyed in these media acts as a diffuser of eating disorders in adolescents. Methodology: 75 articles were selected from Pubmed, Lilacs and Scielo databases in the last 10 years, where after inclusion and exclusion criteria, 20 articles were obtained to compose this review. Results show that social networks expand media expansion so that opinion is encouraged in young people along with psychological support.